Draft Eighth Fiver Year Plan 1990-95 and Annual Plan 1991-92 Volume I Government of Kerala - Planning Commission (Planning Commission, 1990)
Kerala has undergone planned development under seven Five Year Plans and four annual plans during the course of past four decades. In several important respects, Kerala’s development record has been an impressive one. On criteria like adult literacy, life expectancy at birth, female age at marriage and school enrollment ratios, Kerala compares favourably with almost any other region in the developing world. The state has already crossed the national target set for population control for the year 2000. At same time, however, Kerala’s economy has performed poorly in terms of commodity production.
State Planning Board Thiruvananthapuram Government of Kerala